Admission From Nursing Home Residence Increases Acute Mortality After Hip Fractures. (September 2015) - van Dijk, Pim A. D.; Bot, Arjan G. J.; Neuhaus, Valentin; Menendez, Mariano E.; Vrahas, Mark S.; Ring, David
Background: Little is known about the effect of preinjury residence on inpatient mortality following hip fracture. This study addressed whether (1) admission from a nursing home residence and (2) admission from another hospital were associated with higher inpatient mortality after a hip fracture. Methods: Using the National Hospital Discharge Survey database, we analyzed an estimated 2 124 388 hip fractures discharges, from 2001 to 2007. Multivariable logistic regression analysis was performed to identify whether admission from a nursing home and admission from another hospital were independent risk factors for inpatient mortality. Our primary null hypothesis is that there is no difference in inpatient mortality rates after hip fracture in patients admitted from a nursing home, compared to other forms of admission. The secondary null hypothesis is that there is no difference in inpatient mortality after hip fracture in patients whose source of admission was another hospital, compared to other sources of admission. Results: Almost 4% of the patients were admitted from a nursing home and 6% from another hospital. The mean age was 79 years and 71% were women. The majority of patients were treated with internal fixation. Admission from a nursing home residence (odds ratio [OR] of 2.1, confidence interval [CI] 1.9-2.3) and prior hospital stay (OR 3.4, CI 3.2-3.7) were associated with a higher risk of inpatient mortality after accounting for other comorbidities and type of treatment. Conclusions: Patients transferred to an acute care hospital from a long-term care facility or another acute care hospital are at particularly high risk of inpatient death. This subset of patients should be considered separately from patients admitted from other sources. Level of Evidence: Prognostic level II.